Associations between the meniscal lesion parameters and knee joint structures and symptoms in patients with symptomatic knee osteoarthritis - Kaida Bo; Xin Liu; Yuanyi Zhang; Jianliang Ou; Xu Wang; Maolin Yang; Lianhui Zhao; Zhangwei Wu; Jingfeng Liu; Shuo Yang; Wei Zhang; Lelei Zhang; et al. (Arthritis Research & Therapy)
Abstract Background To investigate cross-sectional associations between meniscal lesion parameters and knee joint structures and symptoms in patients with symptomatic knee osteoarthritis (KOA). Methods A total of 102 subjects with symptomatic KOA were included in this study. Coronal magnetic resonance imaging was used to measure the meniscal parameters including the mean distance from medial to lateral meniscal lesions (Mean(MLD)), the mean value of tibial plateau width (Mean(TPW)) and the mean of the relative percentage of the medial to lateral meniscal lesions distance (Mean(RMLD)). The knee structural abnormalities and symptoms included Kellgren-Lawrence grade (KLG), cartilage volume, cartilage defects, bone marrow lesions (BMLs), joint space narrowing (JSN), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), pain, stiffness and physical dysfunction. Results In multivariate analyses, Mean(MLD) and Mean(RMLD) were significantly associated with KLG and were more efficient than cartilage volume and WOMAC in indicating the presence of KOA. The Mean(MLD) was significantly and negatively associated with total cartilage volume [β, 95%CI: -0.008(-0.012, -0.003)], medial tibial joint (MT) cartilage volume [β, 95%CI: -0.012(-0.017, -0.007)] and lateral tibial (LT) cartilage volume [β, 95%CI: -0.006(-0.011, -0.001)], and had positively associations with lateral tibiofemoral joint (LTFJ) cartilage defects, medial tibiofemoral joint (MTFJ) cartilage defects, LTFJ BMLs, and MTFJ BMLs [ORs, 95%CI: 1.063–1.116(1.007–1.059 to 1.119–1.177)] in patients with symptomatic KOA. There were positively associations between Mean(MLD) and WOMAC score [β, 95%CI: 2.145(1.160, 3.131)] in patients with KOA. Furthermore, The Mean(RMLD) was significantly and negatively associated with total cartilage volume [β, 95%CI: -0.005(-0.008, -0.002)], MT cartilage volume [β, 95%CI: -0.008(-0.011, -0.004)] and LT cartilage volume [β, 95%CI: -0.005(-0.008, -0.001)] and had significantly and positively associations with LTFJ cartilage defects, MTFJ cartilage defects, LTFJ BMLs, and MTFJ BMLs [ORs, 95%CI: 1.046–1.086(1.008–1.044 to 1.082–1.123)] in patients with symptomatic KOA. There were positively associations between Mean(RMLD) and WOMAC score [β, 95%CI: 1.465(0.793, 2.136)] in patients with KOA. Conclusions Meniscus lesion parameter values were associated with changes in knee structures and increases in knee symptoms, suggesting that meniscal lesions may contribute to symptoms and structural abnormalities in the knee and increase the risk of KOA.